Monitoring the evolving impact of COVID-19 on institutional surgical services: imperative for quality improvement platforms. Issue 1 (12th December 2020) - Leung, S; Al-Omran, M; Greco, E; Qadura, M; Wheatcroft, M; Mamdani, M; Gomez, D; de Mestral, C
Abstract : The COVID-19 pandemic caused a massive slow down of scheduled surgical services, leading to concerns about increased morbidity from delayed care and of a large backlog of patients. In these times it is critical to collect and monitor data on surgical service volumes to help minimize the consequences to our patients. Here we describe our institutional vascular service volumes through the pandemic to date, demonstrating how quality improvement platforms can be useful tools for proactive data collection and monitoring.. Continued evaluation.